Insanity defense : why our failure to confront hard national security problems makes us less safe - Harman, Jane (St. Martin's Press, 2021)
"Insanity Defense is an insider's account of America's ineffectual approach to some of the hardest defense and intelligence issues in the three decades since the Cold War ended"--